Ecological characteristics of stream reaches with and without low-tech process-based restoration in a wildfire-affected watershed - Nichter, Kimberly Alyse, author; Preston, Dan, advisor; Fairchild, Matthew, committee member; Kanno, Yoichiro, committee member; Morrison, Ryan, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2025)
Wildfires can alter community structure and ecosystem function of montane streams, leading to management challenges. Low-tech process-based restoration (LTPBR) may be a useful tool in post-wildfire catchments, but relatively few studies have examined how LTPBR may influence ecological responses following wildfire. This study compared abiotic and biotic characteristics of a stream reach that received LTPBR, untreated reaches without LTPBR, and a reach with relict beaver activity that had relatively intact berms. All sites had unconfined floodplains and were affected by wildfire four years prior to the surveys. The treatment reach received post-assist log structures two years prior to field surveys. Our objective was to characterize differences in sediment size, water temperature, benthic algae, fine and particulate organic matter, large wood, riparian vegetation, macroinvertebrate communities, and brook trout density and size structure. The relict beaver site had more shallow, lentic habitat, finer substrate, increased particulate organic matter, and greater temperature variability. The untreated reach had a deep, simpler channel, larger substrate, lower particulate organic matter, and more uniform temperatures. The treatment reach had a channel with depth and substrate sizes intermediate between the relict beaver and untreated reaches, higher chlorophyl-a, and moderate temperature variability. Benthic macroinvertebrate biomass and composition varied across habitat types; standing biomass was highest on wood and lotic hard substrates. When scaled to habitat area at the reach scale, macroinvertebrate biomass was highest at the relict beaver reach and comparable at the treatment and untreated reaches. Insect inputs to the stream and emergence showed temporal variation, but did not differ consistently between stream reaches. The treatment reach had slightly higher brook trout density than the other reaches although the most downstream untreated reach had slightly larger fish, particularly in spring. Our results highlight potential differences in stream function and community structure between wildfire-affected streams with and without LTPBR treatments. Continued research on ecological impacts of LTPBR in addition to geomorphic effects may provide valuable insight to success of LTPBR in post-fire watersheds.
Keywords: macroinvertebrate; stream; wildfire; process-based restoration; beaver; trout